Water : the forgotten biological molecule - Bihan, Denis Le , 1957-; Fukuyama, Hidenao (Pan Stanford Publishing, 2010)
Addresses a number of highly topical aspects of a fast emerging field emphasizing some important, but yet unclear roles of water in biological processes, up to brain function. This book intends to bring together multidisciplinary contributions from leading authorities on the properties and the roles of water in cell systems